Therapeutic hypothermia and outcome in hyponatraemic encephalopathy secondary to maternal water intoxication. Issue 3 (17th March 2021) - Alake, Oluwaseyi; Rana, Reena; Jain, Anoo; Chakkarapani, Ela
Abstract : Misguided encouragement to consume large volumes of water during labour for pain relief results in dilutional hyponatraemia in mothers and their babies presenting with neurological dysfunction. We report three babies who were encephalopathic with seizures in the background of hyponatraemia secondary to maternal ingestion of large volumes of water and mild perinatal asphyxia. All babies underwent therapeutic hypothermia in addition to sodium supplementation with fluid restriction. Their neurodevelopment was appropriate for age. This case series highlights the dilemma that could arise with hyponatraemic encephalopathy and mild perinatal asphyxia in the first 6 hours of life, which is the window of opportunity for therapeutic hypothermia for hypoxic-ischaemic encephalopathy. It is important to educate pregnant mothers in labour on the adverse effects of excessive fluid ingestion.